Retiree health benefits and retirement - James Marton; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 2006)
Employer-provided health benefit coverage for workers who retire before age 65 has fallen over the last decade. We examine a cohort of male workers from the Health and Retirement Survey to examine questions about the dynamics of retiree health benefits and the relationship between retiree health benefits and retirement behavior, which is important for the debate over increasing health coverage for older Americans without reducing work incentives. On dynamics, we find that between 1992 and 1996, 24 percent of full-time workers who had retiree health benefits lost their coverage, while 15 percent of full-time workers who lacked coverage gained it. Also, of the full-time employed men who were covered by retiree health benefits in 1992 and had retired by 1996, 3 percent were uninsured, and 15 percent were covered by health insurance other than employerprovided insurance. On the relationship between retiree health benefits and retirement, we find that workers with retiree benefits were 29 to 55 percent more likely to retire than those without. We also find that workers who are eligible for retiree health benefits tend to take advantage of them when they are relatively young.
Keywords: J26; J32; J33; I18; M52; 330; health insurance; employee benefits; retirement; elderly; employment; retiree health benefits; Krankenversicherung; Rentner; Flexible Altersgrenze; Versicherungsschutz; USA